Here comes the sun: residential consumers’ experience with rooftop solar PV in five Indian cities - Devi, A; Narayan, U; Mandal, T (World Resources Institute, 2018)
This working paper documents residential consumers’ experiences with solar rooftop PV systems. The data is captured through household surveys conducted across five Indian cities. The study is an attempt to understand the challenges faced by residential consumers at various stages of their decision pertaining to the installation of rooftop solar PV systems. Key Findings Lack of clear accessible objective information for installation: Overall awareness about solar PV systems among residential consumers is limited. Drawbacks such as absence of clear information about the product, processes, and approvals required for installing the system are the key hurdles. With the lack of credible and objective sources of information, there is strong reliance on vendors as exclusive sources of information. Eﬀorts have been made by nodal agencies at the state and national level to present information about rooftop solar PVs, but they remain elusive since there is a disconnect between the medium of dissemination (which tends to rely predominantly on online platforms and smartphone applications) and the medium of relying on references from friends, family, and neighbors who have already installed solar rooftop systems, which is preferred by consumers. Absence of customized financing options: The local policy and regulatory context, especially with respect to tariﬀs and subsidies, has a significant role to play in determining how a residential consumer considers financing the installation of rooftop PV systems. In the first place, this will determine and inform the consumer decision. Considering a skewed tariﬀ structure, there may be no incentive for a consumer to opt for rooftop PV, which will be a more cost-eﬀective option. Therefore, instruments to finance a product like a rooftop PV system need to be customized to the nature of the product without merely presenting it as another consumer durable good. This is particularly true when it comes to determining loan collateral, which is often disproportionate to the cost of the system. Lack of coordination, institutional priorities and processes: The lack of coordination among the priorities of diﬀerent government agencies has aﬀected the consumer experience. While residents in Chennai encountered an electricity utility that did not support rooftop solar because it conﬂicted with its grid-based power supply, residents in Chandigarh faced challenges in rooftop installations due to restrictions imposed by the municipality’s architectural specifications. In addition, consumers also report challenges faced during institutional processes such as delays, challenges in billing, the need for multiple visits, and the lack of capacity of officials to provide information and guidance.